The Roman annexation of the Nabataean kingdom: a Safaitic witness - Al-Jallad, Ahmad; Macdonald, Michael C. A. (Semitica et Classica, 2024)
Abstract This article presents a new Safaitic inscription dated to the year Gaius Claudius Severus was appointed as governor of the former Nabataean kingdom, called mlkt rbʾl “the kingdom of Rabbʾel.” As such, the text is an important witness to the shadowy events surrounding the Roman annexation of Nabataea in ad 106. Beyond its historical value, the inscription contains a number of hapax legomena, thus expanding our knowledge of the Safaitic lexicon, and its spelling of the Latin name Severus sheds some light on Safaitic phonetics. Abstract Cet article dévoile une nouvelle inscription safaïtique, datée de l’année où Gaius Claudius Severus fut nommé gouverneur de l’ancien royaume nabatéen, appelé mlkt rbʾl « le royaume de Rabbʾel ». Ce texte constitue un témoignage précieux sur les événements obscurs entourant l’annexion romaine de la Nabatène en 106 apr. J.-C. Au-delà de son importance historique, l’inscription contient plusieurs hapax legomena, élargissant ainsi notre connaissance du lexique safaïtique, tandis que son orthographe du nom latin Severus apporte un éclairage nouveau sur la phonétique safaïtique.